Forage productivity in experimental crossbred maize (Zea diploperennis I, D & G) and forage sorghum under rainfed and irrigated conditions in Santa Rosa, La Pampa (Semiárida, 2020)
This paper analyses biomass production (MS kg.ha-1) in experimental forage maize lines by introgression of Z. diploperennis I, D, & G at different cuttíng times under rainfed and irrigated conditions. The lines that produced the highest levels of digestible dry matter in each crop are compared to forage sorghum (brown midrib type) productivity. During the crop's vegetative phase it was found that there was genotype x environment interaction for the total biomass production. Under irrigation L. 212, was favoured, whereas L. 224 was favoured without irrigation. Whole plant dry matter production at ¼ advancement milk lines in grain did not show genotype-environment interaction and lines L. 212, L.224 and L.230a showed a yield statistically similar to that of the tester (DK 780). Production of maize digestible dry matter without irrigation favoured lines L.212, L224 and L. 230a that superseded the yield of the control line, whereas with irrigated condition, the lines that showed the best yield were L.212, L.213 and L.224. L.224 supersedes the DK 780 grain digestible matter under both conditions. Production of digestible dry matter during the grain dough state, without irrigation was similar both for sorghum and maize, but with irrigation it was slightly higher for sorghum. Genetic improvement by means of wide cross-breeding implies incorporating undesirable features in the cultivated crop; however, if it is to be used as forage, as in the case of maize, successful results may be obtained, developing lines that might yield similarly to a commercial hybrid.
Keywords: forage corn; introgression; Zea diploperennis; forage sorghum; rainfed and irrigated condition